(untitled) (Desarrollo, Estado y Espacio, 2024)
This article explores environmental regressions in the protection of forest and wetland ecosystems during the first nine months of Javier Milei’s administration since his inauguration on December 10, 2023. In order to identify regressive policies of an institutional, regulatory and judicial nature, the content of the government regulations published in the Official Gazette of the Nation, which make up the database, has been analysed. In the case of budgetary regressions, the FARN 2024 Budget Monitor was used. This work is based on the recognition of the importance of the principle of non-regression in the Argentine legal system, constitutionally supported and ratified by the Escazú Agreement. In the context of the first government in Argentina openly denying climate change and skeptical about environmental regulation, the principle of non-regression takes on a new urgency.